Biological, Molecular, and Physiological Characterization of Four Soybean Mosaic Virus Isolates Present in Argentine Soybean Crops - Maugeri Suarez, Mariel (2025)
Soybean mosaic virus (SMV) causes systemic infections in soybean plants, leading to chlorotic mosaic and significant yield losses. In Argentina, during the 1990s, three isolates were collected in Marcos Juárez (MJ), Manfredi (M), and Northwestern Argentina (NOA), along with the “Planta Vinosa” (PV) isolate, which causes severe necrosis in some cultivars. These isolates were freeze-dried and stored at −70 °C for several years. They were recovered by mechanical inoculation and biologically, molecularly, and physiologically characterized for the first time. Three of the four isolates showed low genetic divergence in the P1, CI, and CP genes. Although SMV-NOA and SMV-PV had high nucleotide sequence identity, they differed in pathogenicity, seed mottling, and transmission efficiency by seeds or aphids. SMV-NOA caused early changes in photosystem II quantum efficiency (ɸPSII) and malondialdehyde (MDA) content before symptom expression (BS). After symptom development (LS), SMV-M significantly increased MDA, total soluble sugars, and starch compared to the other isolates. Thus, early changes in ɸPSII and sugars may influence late viral symptoms. Likewise, SMV-MJ induced more severe symptoms in the susceptible Davis cultivar than in Don Mario 4800. Therefore, our results demonstrate genomic, biological, and physiological differences among SMV isolates and variable interactions of SMV-MJ with two soybean cultivars.